SISTEM STEGANOGRAPHY DENGAN METODE LEAST SIGNIFCANT BIT (LSB) & METODE CAESAR CIPHER BERBASIS ANDROID - Abrar Hiswara; Aida Fitriyani; Reza Adi Nugraha (Jurnal Informatika, 2020)
This research aims at information security in the form of document files, documents are casual but have a vital role, due to many cyber crimes that try or commit data theft, illegal access or misuse of documents that are used as a particular crime tool. the software development method uses the Rapid Application Development (RAD) model, while the research method applies the Least Significant Bit (LSB) method of hiding information into a digital media (image) as a steganographic technique and Caesar Cipher as a cryptographic technique that encrypts * document filename into aform Caesar randomly characters. The results of the study resulted in an android-based steganography system that uses the Java programming language, as data security for document systems using the least significant bit and caesar cipher method as a top priority and making the system more friendly and interactive to be used easily by users. Steganography system is considered to provide an alternative for users as a system that is able to maintain the confidentiality of documents and provide information to users of the importance of a data security measure.